Pengaruh Story Telling Marketing, Celebrity Endorsment dan Kualitas Produk Terhadap Brand Equity Produk Scarlett Whitening di Kota Rembang - Huda, Misbakhul; Ming Lukiarti, Ming (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
In the research, the problem, the problem studied is about the influence of story telling marketing, celebrity endorsement, and product quality on brand equity Scarlett Whitening products in the city of Rembang. The purpose of why the researchers take the title is to find out how much independent variables to the dependent variable. In this study the metod the researchers use is accidental sampling as a research. By using this metod the researcher determines the criteria of respondents that can be sample in this research that is anyone who happens to meetthe researcher can be used as a sample. Technique used in this research consist of multiple linear regression analysis, Test T, and coefficient of determination test or R2. Based on the results of the research and discussion, it can be concluded that story telling marketing has a significant positive effect on brand equity, celebrity endorsement has a significant positive effect on brand equity, and product quality has an insignificant positive effect on Scarlett Whitening's brand equity.